If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(y + -6) = 28 Reorder the terms: 7(-6 + y) = 28 (-6 * 7 + y * 7) = 28 (-42 + 7y) = 28 Solving -42 + 7y = 28 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '42' to each side of the equation. -42 + 42 + 7y = 28 + 42 Combine like terms: -42 + 42 = 0 0 + 7y = 28 + 42 7y = 28 + 42 Combine like terms: 28 + 42 = 70 7y = 70 Divide each side by '7'. y = 10 Simplifying y = 10
| 5.6+10.5=2.1A | | 8x^2+22x=-5 | | 11x-20=7x-64 | | -(1-7x)-6(-7-x)=36 | | 7x+35=-21 | | 13+2d+4d+3d+9= | | -16b=9 | | y=x^2-6x-3 | | 26+b=20 | | -8x-9x=.66 | | 2a=18 | | 12=x^2-6x | | 3x+9-x=15 | | 36x^2-9x=0 | | 10x^2-8x+1=0 | | 10x^2=58 | | 19x^2=58 | | 24a-22=-49(1-6a) | | 3x+11=-1 | | 16x-3=102-5x | | 107-14-6y=-2(y-4y) | | 60-2x+70-4x=180 | | 4/5/10/6= | | h=3+65t-16t^2 | | h=-16t^2+65t+3 | | -35=-7(5p-5)-5(4p+3) | | -52=-8(4-5n)-4(n-4) | | -1+x^2-1x=0 | | 4(-7+2m)+4(1-m)=-36 | | (80-x)+(90-2x)=180 | | x^2-x=23 | | 79=-5(2x+3)-7(-4+8x) |